2018
DOI: 10.5430/ijhe.v7n4p63
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Unmanned Aircraft Systems to Measure Linear and Areal Features into Undergraduate Forestry Education

Abstract: The use of Unmanned Aircraft Systems (UAS) in undergraduate forestry education continues to expand and develop. Accuracy of data collection is an important aspect of preparation for “society-ready” foresters to meet the complex sustainable environment managing for ecological, social and economic interests.  Hands-on use of a DJI Phantom 4 Pro UAS by undergraduates to measure the length and area of 30 linear features and areal features on Earth’s surface were estimated.  These measurements were compared (measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…These results mirror the results of Viegut et al (2018) that found no significant difference between Pictometry and Google Earth Pro, but both were statistically more accurate than the DJI Phantom 4 Pro UAS. This study reinforces the accuracy of Pictometry and Google Earth for area measurements and the value of student-driven hands on research in spatial science assessments.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These results mirror the results of Viegut et al (2018) that found no significant difference between Pictometry and Google Earth Pro, but both were statistically more accurate than the DJI Phantom 4 Pro UAS. This study reinforces the accuracy of Pictometry and Google Earth for area measurements and the value of student-driven hands on research in spatial science assessments.…”
Section: Discussionsupporting
confidence: 84%
“…Undergraduate spatial science students produced accurate onscreen digitizing of rectangles with minimal instruction, crucial for measuring quantitative data for natural resource planning (Unger et al, 2014;Viegut et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kulhavy, Unger, Hung and Douglass (2014) found Pictometry ® was more accurate than LIDAR data in assessing height measurements; and baldcypress tree heights (Unger, Hung, & Kulhavy, 2014). Pictometry ® did not differ from Google Earth measures but did from Unmanned Aerial Systems from a DJI Phantom 4 Pro drone (Viegut, Kulhavy, Unger, Hung, &Humphreys, 2018).…”
Section: Journal Of Studies In Educationmentioning
confidence: 99%